Pola Kepemimpinan Di Pondok Pesantren Dalam Prespektif Milenial - Wafiyatu Maslahah (Social, Humanities, and Educational Studies (SHES): Conference Series, 2022)
The research aims to: 1.) determine the role of pesantren in the millennial perspective, and 2.) determine the pattern of leadership in Islamic boarding schools in the millennial perspective. It is interesting to study the development of Islamic boarding schools in the millennial era as a legacy of education during the Islamic era, particularly its role in the millennial perspective and its leadership pattern. The qualitative research method was used in this study. All leaders, caregivers, teachers, residents near the Islamic boarding school, and students at Pondok Pesantren Assalam Jambewangi Selopuro Blitar comprise the research population. Purposive random sampling was used to select the research sample. Interviews, observations, and documentation are used to collect research data. Data triangulation is used to verify the accuracy of the data. This research yielded the following findings is Islamic boarding schools, in their role in the millennial era, can keep up with the times. still exist and are improving. This Islamic Boarding School is a salafiyah that can keep up with the times as well as Science and Technology without departing from the existing guidelines. Without departing from the rules enshrined in Islam's teachings.